The Influence of Providing Education About First Aid Syncope Using the Demonstration Method on Students' Level of Knowledge at SMP Muhammadiyah 1 Yogyakarta - Pratiwi, Riska Yunia; Muhaji; Nia Handayani (Jurnal Kesehatan Cendikia Jenius, 2024)
Syncope or fainting often occurs suddenly, syncope can be caused by the sufferer being in the hot sun for too long. This study aims to determine the effect of providing education about syncope first aid using the demonstration method on the level of knowledge of students at SMP (Junior High School) Muhammadiyah 1 Yogyakarta.This research method applied a quantitative method with a pre- experimental design with one group pre-test post-test design. The sampling technique used a probability sampling technique with proportionate stratified random sampling totaling 80 respondents. The data collection method implied and data processing in this research uses the Wilcoxon test. Test results were obtained to determine the effect of providing education about syncope first aid using the demonstration method on the level of knowledge of students at SMP Muhammadiyah 1 Yogyakarta using the Wilcoxon test. There is an effect of providing education about syncope first aid using the demonstration method on the level of knowledge of students at SMP Muhammadiyah 1 Yogyakarta with the Wilcoxon test showing a p-value of 0.000<0.005.